Accuracy of self-report of on-road crashes and traffic offences in a cohort of young drivers: the DRIVE study. Issue 4 (26th April 2010) - Boufous, Soufiane; Ivers, Rebecca; Senserrick, Teresa; Stevenson, Mark; Norton, Robyn; Williamson, Ann
Abstract : In order to determine the accuracy of self-report of on-road crashes and traffic offences among participants in the DRIVE study, 2991 young drivers in New South Wales, Australia who completed the follow-up questionnaire were asked whether they had been involved in an on-road crash or were convicted for a traffic offence while driving during the year prior to the survey. This information was linked to police crash data to determine the level of accuracy of self-report of on-road crashes. There was a high level of accuracy in young drivers' self-report of police recorded crashes (85.1%; 95% CI 78.2% to 92.1%) and of police recorded traffic offences (83.0%; 95% CI 79.4% to 86.6%). Results suggest that surveys may be useful tools for estimating the incidence of on-road crashes and traffic offences in young drivers. The findings are particularly relevant to jurisdictions where access to administrative data is limited.